2011
DOI: 10.1111/j.1475-4983.2011.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Emsian Rutoceratoidea (Nautiloidea) from the Prague Basin, Czech Republic: morphology, diversity and palaeoecology

Abstract: Nautiloids of the superfamily Rutoceratoidea from the late Emsian (late Early Devonian) of the Prague Basin (Czech Republic) are commented upon. Species recognized include the hercoceratids Hercoceras mirum, H.? transiens, Ptenoceras proximum, P. nudum, P. minusculum and Anomaloceras anomalum, as well as the rutoceratids Adelphoceras bohemicum, Homoadelphoceras devonicans, Pseudorutoceras bolli and Goldringia? devonicans. In addition, four new species are described: Parauloceras regulare sp. nov., Roussanoffoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…raised metabolic activity of the organism after hatching. A positive correlation between sculpture development and original content of calcium carbonate in seawater is highly probable (Graus 1974, Vermej 1987, Manda & Turek 2011. This is supported by the development of sculpture in specimens coming from different depth-related facies.…”
Section: Hatching Indication Inferred From Shell Morphology Summarysupporting
confidence: 51%
See 1 more Smart Citation
“…raised metabolic activity of the organism after hatching. A positive correlation between sculpture development and original content of calcium carbonate in seawater is highly probable (Graus 1974, Vermej 1987, Manda & Turek 2011. This is supported by the development of sculpture in specimens coming from different depth-related facies.…”
Section: Hatching Indication Inferred From Shell Morphology Summarysupporting
confidence: 51%
“…The difference in sculpture in conchs from shallow and deeper water settings documents partial limited migrations between populations of Ophioceras, a feature known so far only from Early Devonian oncocerid Ptenoceras Hyatt, 1894 (Manda & Turek 2011). A more prominent fine sculpture may be a phenotypic reaction to living in a more turbulent shallow-water domain.…”
Section: Autecology Of Specimens Reaching Coiled Conch Stagementioning
confidence: 99%
“…From Table 1, we infer that the RHf nautiloid assemblage represented part of a localized, biohermal community occurring along the lower shoreface of an inner shelf patch reef and was comprised of a diverse and abundant array of benthopelagic animals (e.g., Brett et al, 2007;Barskov et al, 2008;Manda and Turek, 2011). Other cooccurring and disarticulated benthic invertebrates including brachiopods, corals, and trilobites support this interpretation (Williams, 1980;Fagerstrom, 1983;Brett and Baird, 1986;Kaufmann, 1998;Becker and Bartholomew, 2013).…”
Section: Depositional Environment Of Rhf Nautiloidsmentioning
confidence: 81%
“…An alternative explanation proposed in this study for the large size of the nautiloids found in the RHf assemblage and Table 1 may be related to a life and reproductive strategy in which small juveniles lived separately and in a different depositional environment. Examples of juvenile and adult nautiloids from the Devonian occurring in different depositional environments that support this explanation include: 1) Wadleigh Formation of southeastern, Alaska, and Holy Cross Mountains near Chęciny, Poland, that contain multiple beds and concretions of concentrated juvenile nautiloids (Soja et al, 1996;Rakociński and Borcuch, 2016); 2) Cherry Valley Limestone of central New York that contains concentrations of large co-occurring orthoconic nautiloids and ammonoids (Klofak, 2002); and, 3) Třebotov and Choteč Limestones of the Prague Basin, Czech Republic that contains both juvenile and adult coiled nautiloids separated into distinct size populations (Manda and Turek, 2011). Proposed life and reproductive strategies in these studies that resulted in separation of juvenile and adult populations included: spawning, predation, and the efficiency of calcification in embryonic nautiloids in warm shallow water.…”
Section: Nautiloid Concentration and Size Classmentioning
confidence: 99%
“…This is particularly true for ammonoids in which the strategy of early ontogenetic stages (expressed in protoconch and ammonitella size, shape, and ornament) was crucial for survival through extinction events and consequent quick radiation of survivors in contrast to slow recovery of nautiloid fauna (House 1996, Manda & Turek 2011.…”
mentioning
confidence: 99%